2014
DOI: 10.1242/dmm.017038
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord pathology is ameliorated by P2X7 antagonism in SOD1-G93A mouse model of amyotrophic lateral sclerosis

Abstract: In recent years there has been an increasing awareness of the role of P2X7, a receptor for extracellular ATP, in modulating physiopathological mechanisms in the central nervous system. In particular, P2X7 has been shown to be implicated in neuropsychiatry, chronic pain, neurodegeneration and neuroinflammation. Remarkably, P2X7 has also been shown to be a ‘gene modifier’ in amyotrophic lateral sclerosis (ALS): the receptor is upregulated in spinal cord microglia in human and rat at advanced stages of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 50 publications
13
115
2
Order By: Relevance
“…This is consistent with our previous results showing that inhibition of P2X7 during a well-defined phase of ALS disease exerts neuroprotection and reduces neuroinflammation [40]. Given the wellrecognized role of P2X7 in the progression of inflammation [41], this also suggests that P2X7 might act as a M1 marker at least in ALS spinal cord at end stage.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with our previous results showing that inhibition of P2X7 during a well-defined phase of ALS disease exerts neuroprotection and reduces neuroinflammation [40]. Given the wellrecognized role of P2X7 in the progression of inflammation [41], this also suggests that P2X7 might act as a M1 marker at least in ALS spinal cord at end stage.…”
Section: Discussionsupporting
confidence: 92%
“…Although NOX2 is an important mechanism in ALS pathogenesis [42], we have recently demonstrated that NOX2 blockade is not sufficient to prolong survival in SOD1 G93A mice [40]. This is consistent with the lack of beneficial therapeutic effects provided by NOX2 inhibitors [43] and in agreement with the present data showing that clemastine, while inhibiting NOX2, only slightly improved ALS pathological symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…and i.p. administration following the reports of Marques et al 17) and Apolloni et al, 34) and its optimum dose was judged to be 250 mg/kg (p.o.) (data not shown).…”
Section: Chemicalsmentioning
confidence: 99%
“…Furthermore there is a temporal effect in pre-symptomatic stages P2XR promotes survival of neurons but in symptomatic phase their activation is associated to increased cell death [93]. These differential effects of ATP and P2XR could be associated with different types of receptors, and in literature is reported that at least P2X4 and 7 are involved in the disease [92,94], and this could help to explain the dual effect of ATP in ALS.…”
Section: Purinergic Receptors and Neurodegenerative Disordersmentioning
confidence: 99%